Secondary aphakic glaucoma in children: a 15-year retrospective study - N.N. Sadovnikova; V.V. Brzheskiy; M.A. Zertsalova; A.Yu. Baranov (РМЖ "Клиническая офтальмология")
N.N. Sadovnikova, V.V. Brzhesky, M.A. Zertsalova, A.Yu. Baranov St. Petersburg State Pediatric Medical University, St. Petersburg, Russian Federation Aim: to assess the incidence of glaucoma in children who underwent congenital cataract surgery, to determine the risk factors for its development. Patients and Methods: this retrospective study included 206 children (301 eyes) aged 10 years or less who underwent congenital cataract surgery in the Ophthalmology Department of St. Petersburg State Pediatric Medical University (SPbGPMU) with an average follow-up period of 8.8±0.2 years. The children were divided into 4 groups by age at the surgical procedure. Group 1 included children operated on at the age of 90 days and younger; group 2 — aged from 91 to 365 days; group 3 — from 1 year to 4 years 11 months 29 days old; group 4 — from 5 to 10 years old. Co-existing ocular disorders were present in 247 (82,1%) eyes. Co-occurring extraocular disorders were found in 52 (25,2%) of 206 operated patients. Results: by the last visit, no patient in group 4 developed glaucoma. Glaucoma was diagnosed in 21 eyes (27.3%) of 14 patients from group 1, in 16 eyes (21.1%) of 12 patients from group 2 and in 10 eyes (12.5%) of 8 patients from group 3. In 57.4% of cases, glaucoma was controlled with medications, and surgery was performed on 20 eyes, including sinus trabeculectomy and Ahmed valve implantation. Statistically significant risk factors for the development of secondary glaucoma encompassed cataract extraction in children younger than 1 year of age, microcornea, additional intraocular surgical interventions, and aphakia. Conclusion: a less effective visual outcome of aphakic glaucoma treatment is caused by multiple factors, including amblyopia, nystagmus, as well as delayed diagnosis and untimely surgical intervention. Thus, to ensure early diagnosis of glaucoma, it is necessary to put tonometry and measurement of the axial length of the eye on the list of diagnostic tools for the outpatient follow-up of patients who underwent congenital cataract surgery. Keywords: aphakic glaucoma, congenital cataract, Ahmed valve, Cataract extraction, microcornea, aphakia, intraocular surgical interventions. For citation: Sadovnikova N.N., Brzhesky V.V., Zertsalova M.A., Baranov A.Yu. Secondary aphakic glaucoma in children: a 15-year retrospective study. Russian Journal of Clinical Ophthalmology. 2023;23(2):80–85 (in Russ.). DOI: 10.32364/2311-7729-2023-23-2-80-85.